2023
DOI: 10.2147/ccid.s443128
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Relationship Between Alcohol Consumption and Skin Diseases

Lin Liu,
Jin Chen

Abstract: Throughout history, alcohol consumption has been an integral part of human culture. Alcohol consumption, alcoholism in particular, influences the onset and progression of liver diseases, neurological disorders, and multiple types of cancer. However, the role of alcohol consumption in influencing skin diseases has often been overlooked. In this review, we present the progress of research investigating the effects and potential mechanisms of action of alcohol consumption on acne, rosacea, psoriasis, atopic derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Alcohol intake seems to play a role as a possible determinant for acne. Many crossborder investigations in European and Asian populations have demonstrated that alcohol abusers have a markedly greater prospect of acne than abstainers [67,68,[90][91][92]. However, Shen et al showed that the prevalence of acne among people over 25 years of age was 5.5% in chronic alcoholics, 5.8% in moderate drinkers, and 5.5% in abstinents, which would suggest that alcohol does not seem to be a determinant for acne among adults [93].…”
Section: Other Products That Can Worsen Acnementioning
confidence: 99%
“…Alcohol intake seems to play a role as a possible determinant for acne. Many crossborder investigations in European and Asian populations have demonstrated that alcohol abusers have a markedly greater prospect of acne than abstainers [67,68,[90][91][92]. However, Shen et al showed that the prevalence of acne among people over 25 years of age was 5.5% in chronic alcoholics, 5.8% in moderate drinkers, and 5.5% in abstinents, which would suggest that alcohol does not seem to be a determinant for acne among adults [93].…”
Section: Other Products That Can Worsen Acnementioning
confidence: 99%